The effect of sugar-free and sugar chewing gums on plaque deposition - Pradeep Tangade; Anmol Mathur; Shikha Chaudhary; Rahul Gupta (Wolters Kluwer Medknow Publications, 2012)
Background: Chewing gum is a habit practiced regularly by a relatively high proportion of individuals in many countries including India, and its use has increased within the last decade. The aim of this study was to determine the effects of sugar-free and sugar chewing gums on plaque deposition. Materials and Methods: The study is a double blind clinical trial involving 16 healthy volunteers (divided into 2 groups) in a 4-day plaque regrowth model. On day one, subjects received professional prophylaxis, suspended oral hygiene measures, and commenced chewing their allocated product. Gum chewing was one piece chewed for 30 minutes 3 times a day. On day 5, subjects were scored for plaque with the help of Silness and Loe Index. Results: Results show sugar-free group have a lesser mean plaque score of 0.98 as compare to sugar group (1.23), though this difference was not statistically significant. Conclusion: The sugar-free gums can be used as an adjunct to mechanical oral hygiene measures.